2012
DOI: 10.1177/0363546512459476
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Future ACL Injury Risk After ACL Reconstruction in Soccer Athletes From the Multicenter Orthopaedic Outcomes Network (MOON) Group

Abstract: Background There is limited information on outcomes and return to play (RTP) after ACL reconstruction (ACLR) in soccer athletes. Hypothesis The purpose of this study was to (i) test the hypotheses that player sex, side of injury and graft choice do not influence RTP, and (ii) define the risk for future ACL injury in soccer players after ACLR. Study design Retrospective cohort study, Level II. Methods Soccer players in a prospective cohort were contacted to determine RTP following ACLR. Information regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
278
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(308 citation statements)
references
References 33 publications
16
278
4
3
Order By: Relevance
“…Despite many reports of successful outcomes following ACL reconstruction, recent reports have suggested that the rates of return to sport may not match the success of this surgery as measured by other factors [2,4,5,10,13,19,25,31,44]. This discrepancy raises many issues and the purpose of this article is to explore return to sport following ACL reconstruction from a number of perspectives.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite many reports of successful outcomes following ACL reconstruction, recent reports have suggested that the rates of return to sport may not match the success of this surgery as measured by other factors [2,4,5,10,13,19,25,31,44]. This discrepancy raises many issues and the purpose of this article is to explore return to sport following ACL reconstruction from a number of perspectives.…”
Section: Discussionmentioning
confidence: 95%
“…Mascarenhas et al found that 50 % of young (25 years or less at the time of ACL reconstruction) athletes returned to their pre-injury sport at some stage following surgery [31]. Brophy et al reported that at a mean follow-up of seven years 36 % of soccer players were still playing compared to the 72 % that had resumed play at some time following their ACL reconstruction [10]. Similarly, Struewer et al reported that the participation rate in pivoting and contact sports decreased from 78 % at two years to 45 % at 13.5 years, and for competitive sport from 65 % to 19 % [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S, ACL injury rate is almost 1 in 3500 individuals every year [1] which is calculated to approximately 125000 to 200000 ACL reconstructions yearly. Many studies have examined the injury rate in football and they reported that from all injuries, 60% to 80% occur in lower extremities [2][3][4]. Most of these injuries are knee or ankle related 29% and 19% respectively [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these injuries are knee or ankle related 29% and 19% respectively [2]. From these knee injuries Anterior Cruciate Ligament (ACL), Posterior Cruciate Ligament (PCL) and Medial Collateral Ligament (MCL) are considered to be most frequent and severe [3,4]. possibilities to get reinjured than patients of an older age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation